2010
DOI: 10.1007/s11104-010-0588-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil strength in the rooting zone of wheat

Abstract: When roots abstract water thus drying the soil, crop growth may be reduced by increasing strength of soil as well as the lack of water. Strong soil impedes root growth, restricting access to deeper water. As a result, there is a need to estimate soil strength in order to model crop response to dry soil correctly. The strength of soil can be routinely assessed with a penetrometer but measurements are time consuming and hard work to acquire at the frequency required to understand soil-water-plant relations. To m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Waines and Ehdaie [25] conclude that the root systems of modern wheat cultivars are small, having perhaps two thirds of the root mass of the landraces from which they derive. Whitmore et al [26] argue that the physical impediment to root growth is a more significant stress than the lack of accessibility of water. There thus seems scope for breeding to improve nutrient acquisition and to reduce other constraints to maximum yield and nutrient uptake such as water stress.…”
Section: Remove Constraints (D)mentioning
confidence: 99%
“…Waines and Ehdaie [25] conclude that the root systems of modern wheat cultivars are small, having perhaps two thirds of the root mass of the landraces from which they derive. Whitmore et al [26] argue that the physical impediment to root growth is a more significant stress than the lack of accessibility of water. There thus seems scope for breeding to improve nutrient acquisition and to reduce other constraints to maximum yield and nutrient uptake such as water stress.…”
Section: Remove Constraints (D)mentioning
confidence: 99%
“…Although, S is widely used to estimate x (e.g. Whitmore et al, 2011) an alternative has been suggested by Khallili and Khabbaz (1998) who proposed that…”
Section: Introductionmentioning
confidence: 99%
“…This beneficial effect is due to several factors including the higher volume explored by the roots (Zhang et al, 2004) and the higher soil volume with no mechanical restrictions (Whitmore et al, 2011). The increase in the fertilization rate also had an effect on grain yield; there were differences in production associated with effective soil depth ( Figures 2a and 2b) when taking into consideration the greater root exploratory capacity and its relationship with the recovery of applied nutrients (Richards, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Busscher et al (2001) mention that corn (Zea mays L.) yield is limited by deep compacted strata because these reduce root exploration within the soil profile. Similarly, Whitmore et al (2011) point out that wheat production is limited by soil mechanical resistance, a factor that is part of the root environment. Various studies of soil profile reserve indicate that determining nutrient availability in the superficial stratum (0-20 cm) is an inadequate indicator of the soil chemical properties or the effect of residual fertilization from the previous crop (Eghball et al, 2003;Hirzel et al, 2007;Li et al, 2011); this suggests the need to monitor these properties within the root-explorable soil profile.…”
Section: Introductionmentioning
confidence: 99%